2011
DOI: 10.1097/prs.0b013e31821740cc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteogenesis and Survival within Bone Grafts to the Calvaria: The Effect of the Dura versus the Pericranium

Abstract: The dura and pericranium each contributed to osteogenesis, although dural contact was more effective. Maintenance of dural contact enhanced osteogenesis through the entire graft, whereas pericranial contact enhanced osteogenesis only on the pericranial surface of fresh grafts. These data suggest dura is largely responsible for cranial graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
0
30
1
1
Order By: Relevance
“…2,[25][26] Exogenous growth factors (eg, BMP) applied to the dura may enhance this osteogenic potential, as does mechanical separation, or tenting membranes over the dura. 2,[28][29][30][31][32] However, the osteogenic role of dura and scalp periosteum has not been investigated during cranial distraction. Typically, the regenerate accounts for the majority of new bone growth, but we postulate that the subjacent osteogenic dura positively modulates the process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2,[25][26] Exogenous growth factors (eg, BMP) applied to the dura may enhance this osteogenic potential, as does mechanical separation, or tenting membranes over the dura. 2,[28][29][30][31][32] However, the osteogenic role of dura and scalp periosteum has not been investigated during cranial distraction. Typically, the regenerate accounts for the majority of new bone growth, but we postulate that the subjacent osteogenic dura positively modulates the process.…”
Section: Discussionmentioning
confidence: 98%
“…31,33 Our purpose to implement them in this study was to identify and distinguish bone formation from all potential sites (periosteum, dura, regenerate, native bone marrow). As expected, we found that the callus behind the trailing edge of the transport segment was the principal contributor to osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This remained clinically irrelevant but seems to confirm that periosteal coverage might have a positive effect [2, 18]. We think that preservation of the periosteum during decompressive craniectomy could be advantageous for a future cranioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of strong and thick adult bone makes natural partial reabsorption unlikely or at least limits it. Finally, like all biomaterials, graft coverage by vital pericranium may play a role in decreasing the reabsorption risk [2, 18], though its efficacy remains unproven.…”
Section: Discussionmentioning
confidence: 99%
“…Falhas ósseas induzidas na região da calvária sob a influência da dura-máter e periósteo também tendem a apresentar volume de osso neoformado significativamente maior do que falhas ósseas em outras regiões, como, por exemplo, a região maxilar e alveolar sem a influência do efeito osteoindutor da dura-máter. 77 Essas três variáveis relacionadas ao modelo animal podem interferir no sucesso de uma terapia de bioengenharia de tecidos ósseos. Portanto, a padronização das dimensões de uma falha óssea induzida, bem como da espécie e idade do modelo animal são essenciais para testar fontes promissoras de CTM e novos biomateriais carreadores.…”
Section: Conceito De Falha óSsea Críticaunclassified